The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1016/j.ebiom.2015.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Liposomal Nanoparticles of a Spleen Tyrosine Kinase P-Site Inhibitor Amplify the Potency of Low Dose Total Body Irradiation Against Aggressive B-Precursor Leukemia and Yield Superior Survival Outcomes in Mice

Abstract: This study was designed to improve the efficacy of radiation therapy against radiation-resistant leukemia. We report that the potency of low dose radiation therapy against B-precursor acute lymphoblastic leukemia (BPL) can be markedly enhanced by combining radiation with a liposomal nanoparticle (LNP) formulation of the SYK-P-site inhibitor C61 (“C61-LNP”). C61-LNP plus low dose total body irradiation (TBI) was substantially more effective than TBI alone or C61-LNP alone in improving the event-free survival ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…The anti-leukemic activity of CD22-RTM against leukemic stem cells was studied in a previously published NS mouse xenograft model of human B-lineage ALL ( Uckun et al, 2013 , Uckun et al, 2015b , Uckun et al, 2015c ). The research was approved by the IACUC of CHLA.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The anti-leukemic activity of CD22-RTM against leukemic stem cells was studied in a previously published NS mouse xenograft model of human B-lineage ALL ( Uckun et al, 2013 , Uckun et al, 2015b , Uckun et al, 2015c ). The research was approved by the IACUC of CHLA.…”
Section: Methodsmentioning
confidence: 99%
“…For multiple group comparisons, significant treatment effects were determined using linear contrasts for all pairwise comparisons defined by an ANOVA model with one fixed factor for treatment (6 comparisons for a model consisting of 4 treatment groups: untransfected cells (N = 5), cells transfected with CD22-RTM (N = 17), EPL (N = 17), or Dystrophin-RTM (N = 5)). Two separate models were constructed for spleen size and log 10 transformed nucleated spleen cell counts using previously published standard procedures ( Uckun et al, 2013 , Uckun et al, 2015c ). Comparisons of 2 treatment groups (pooled controls (N = 27) versus CD22-RTM treated (N = 17)) were performed using a two-tailed T -test.…”
Section: Methodsmentioning
confidence: 99%
“…Uckun et al demonstrated higher expression of SYK in B-ALL in early relapse and reported that the encapsulation of C61, an inhibitor of SYK phosphorylation, into liposome had a potent anti-leukemic activity [149]. Further study revealed that the combination of this approach with low dose total body irradiation (TBI) could remarkably deplete refractory B-ALL clone and leading to higher OS compared to TBI and C61-liposome alone [150].…”
Section: Nanosystems In the Treatment Of Lymphoid Malignanciesmentioning
confidence: 99%
“…Data mining, bioinformatics, computational modeling and simulation have increasingly become integral to development of novel hypotheses in disease progression and potentially novel therapeutic innovations that target prominent receptors in leukemias (CD19 and CD22 receptors) to eradicate cancer cells. [14][15][16][17][18][19][20] Our project attempted to link data mining efforts that identify genetic signatures in high risk patient sub-groups to data explorations methods developed using R made available in Bioconductor (http://www.bioconductor. org/) by writing interactive, exploration based statistical analysis platform provided by Shiny applications (http://shiny.rstudio.com/).…”
Section: -9mentioning
confidence: 99%